E-learning -- effective, engaging, entertaining (and earthquake proof) : a thesis presented in partial fulfilment of the requirements of the degree of Master of Education (Adult Education) at Massey University, Extramural, New Zealand - Cruickshank, Alice (Massey University, 2013)
This study is concerned with what makes e-learning effective and engaging as a workplace professional development tool. Using the example of a workplace e-learning programme in Christchurch City Libraries, the study considers the whole process from development of the programme to delivery and evaluation and asks what factors impact upon effectiveness and engagement in a workplace e-learning programme. A number of factors including the organisational culture and workplace environment, the development process, the learning environment, learner support, the e-learning environment and specific e-learning activities were examined. The study itself took place over a unique period of time as Christchurch recovered from several devastating earthquakes. The impact of the disaster and recovery process on the programme and the effectiveness of e-learning in a post-disaster environment is also explored. This study uses a Participatory Action Research approach with data collected and analysed from a variety of sources including interviews with programme developers, pre- and post-course questionnaires, online activity tracking tools, forum posts, trainee learning logs, the researcher’s reflective journal, and a participant focus group. The findings from the study suggest a number of elements that contribute to effective and engaging e-learning programmes in the workplace: a) workplace support of the programme by team leaders is essential but the trainee also needs to be in a position to negotiate for the actual time and resources required. b) Developing an online programme requires a different approach and skill set than designing and delivering face-to-face training and may best be managed as a product development project. c) The attractiveness and ease of navigation are important factors for trainees’ engagement with e-learning. d) Short, locally made videos of real-life workplace scenarios proved to both effective and engaging with trainees able to transfer skills to the workplace. e) A wide variety of e-learning activities promoted interest and engagement among learners. f) Consideration needs to be given to how workplace e-learning is evaluated to ensure skill transfer to the workplace is taking place.
Keywords: Christchurch City Libraries; Officials and employees; Training of; Computer-assisted instruction; Library employees; Employees; New Zealand